2010
DOI: 10.1016/j.atmosenv.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol properties, in-canopy gradients, turbulent fluxes and VOC concentrations at a pristine forest site in Amazonia

Abstract: a b s t r a c tAerosol physical and chemical properties were measured in a forest site in central Amazonia (Cuieiras reservation, 2.61S; 60.21W) during the dry season of 2004 (AugeOct). Aerosol light scattering and absorption, mass concentration, elemental composition and size distributions were measured at three tower levels (Ground: 2 m; Canopy: 28 m, and Top: 40 m). For the first time, simultaneous eddy covariance fluxes of fine mode particles and volatile organic compounds (VOC) were measured above the Ama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
56
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 60 publications
12
56
0
1
Order By: Relevance
“…Median particle number concentration reaches 1254 (557-2928) cm −3 (Table 1). The values are compatible with previously reported values for dry season from another site in the same forest reservation (ZF2) (averages in the range of 1080 to 1400 cm −3 , according to 5 Rissler et al, 2004;Rizzo et al, 2010). In spite of the three fold increase from wet to dry season, observed particle number concentrations are well below the observations in the Amazonian state of Rondônia for example, a site heavily affected by biomass burning emissions where particle number concentration averages in the range of 5700 to 10440 cm To analyze dynamic variations of the particle number size distributions, one to three lognormal modes were fitted to each size spectra.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Median particle number concentration reaches 1254 (557-2928) cm −3 (Table 1). The values are compatible with previously reported values for dry season from another site in the same forest reservation (ZF2) (averages in the range of 1080 to 1400 cm −3 , according to 5 Rissler et al, 2004;Rizzo et al, 2010). In spite of the three fold increase from wet to dry season, observed particle number concentrations are well below the observations in the Amazonian state of Rondônia for example, a site heavily affected by biomass burning emissions where particle number concentration averages in the range of 5700 to 10440 cm To analyze dynamic variations of the particle number size distributions, one to three lognormal modes were fitted to each size spectra.…”
supporting
confidence: 92%
“…Observations have shown that sulfuric acid, amines and organic vapor play a key role in the activation and subsequent growth of particle clusters (Almeida et al, 2013;Ehn et al, 2014;Kulmala et al, 2013;Paasonen 5 et al, 2010). NPF have been observed worldwide and in different environments (Kulmala et al, 2004), but several intensive experiments have shown that in Amazonia nucleation and subsequent particle growth is rare inside the boundary layer (BL) (Rissler et al, 2004;Rizzo et al, 2010;Zhou et al, 2002). Since the occurrence of NPF may depend on season and location (i.e., may vary depending on atmospheric conditions), short duration experiments cannot be conclusive about its frequency in Amazonia.…”
Section: Introductionmentioning
confidence: 99%
“…However, upward particle fluxes often appeared in the morning. Rizzo et al (2010) also observed upward particle number fluxes in the morning simultaneously with increasing particle number concentration, during aerosol flux measurements in the dry season at another tower at the same site. These early morning upward fluxes may have been related to primary biogenic aerosol emission of particles that have been stored in the canopy throughout the night, similar to CO 2 (Goulden et al, 2006;Araújo et al, 2008;Tóta et al, 2008), and the fact that these upward fluxes were sometimes correlated with increasing number concentrations suggest that they cannot be explained only as a result of dilution caused by entrainment during mixed layer growth.…”
Section: Introductionmentioning
confidence: 59%
“…Estudos confirmam a Amazônia como um potencial emissor de material particulado biogênico (GRAHAM et al, 2003;ANDREAE, 2007;RIZZO et al, 2010), mas há também a contribuição de partículas emitidas pela queima de biomassa que influenciam fortemente as taxas fotossintéticas que afetam o balanço regional de carbono (OLIVEIRA et al, 2007). Sendo também responsáveis por alterações no balanço radiativo da atmosfera (RAMANATHAN et al, 2001).…”
Section: Introductionunclassified